PTEN/PI3K/Akt pathway alters sensitivity of T-cell acute lymphoblastic leukemia to L-asparaginase - Hlozkova, Katerina; Hermanova, Ivana; Safrhansova, Lucie; Alquezar-Artieda, Natividad; Kuzilkova, Daniela; Vavrova, Adela; Sperkova, Kristyna; Zaliova, Marketa; Stary, Jan; Trka, Jan; Starkova, Julia (Scientific reports, 2022)
Childhood T-cell acute lymphoblastic leukemia (T-ALL) still remains a therapeutic challenge due to relapses which are resistant to further treatment. L-asparaginase (ASNase) is a key therapy component in pediatric T-ALL and lower sensitivity of leukemia cells to this drug negatively influences overall treatment efficacy and outcome. PTEN protein deletion and/or activation of the PI3K/Akt signaling pathway leading to altered cell growth and metabolism are emerging as a common feature in T-ALL. We herein investigated the relationship amongst PTEN deletion, ASNase sensitivity and glucose metabolism in T-ALL cells. First, we found significant differences in the sensitivity to ASNase amongst T-ALL cell lines. While cell lines more sensitive to ASNase were PTEN wild type (WT) and had no detectable level of phosphorylated Akt (P-Akt), cell lines less sensitive to ASNase were PTEN-null with high P-Akt levels. Pharmacological inhibition of Akt in the PTEN-null cells rendered them more sensitive to ASNase and lowered their glycolytic function which then resembled PTEN WT cells. In primary T-ALL cells, although P-Akt level was not dependent exclusively on PTEN expression, their sensitivity to ASNase could also be increased by pharmacological inhibition of Akt. In summary, we highlight a promising therapeutic option for T-ALL patients with aberrant PTEN/PI3K/Akt signaling.
Keywords: fosfohydroláza PTEN; Child; PTEN Phosphohydrolase; lymfoblastická leukemie-lymfom z prekurzorových T-buněk; signální transdukce; Signal Transduction; protoonkogenní proteiny c-akt; T-lymfocyty; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-akt; Humans; T-Lymphocytes; lidé; asparaginasa; Asparaginase; fosfatidylinositol-3-kinasy; dítě; Phosphatidylinositol 3-Kinases